Permainan Kooperatif Untuk Menilai Kualitas Pertemanan: Studi Eksperimental Pada Mahasiswa di Kota Batam - Anggriani Adnas, Diny; Phua, Gary (UNIVERSITAS STEKOM, 2023)
Video games are a form of entertainment that are very popular with the primary reason people play games being for social reasons that resulted in the co-op genre becoming one of the most popular genres to be played. The aim of this research is to see analyze the viability of using cooperative video games specifically overcooked! 2 as a way of getting players to show certain behaviors that can be used to assess their friendship quality and also to see whether playing together has an effect towards the friendship quality between friends. This research will be done using an experimental method in which the writer will observe the players throught their session and following up with an interview. After the experiment was completed the author was able to reach the conclusion that cooperative video games can be used to bring out behaviors that can be used evaluate friendship quality and also effect friendship quality even if only temporary.